Video Theraphy: The use of audiovisual media for therapeutic purposes - Adriana Farías; Marcelo González Magnasco (Arteterapia)
This article is about the experience of the workshop of Video therapy, which is carried out since 2008 in the Day Hospital Service at the Hospital Psicoasistencial interdisciplinary José T. Borda, in the city of Buenos Aires, Argentina. In it we consider the main theoretical aspects that have served as the basis for our work, the specific characteristics that make the context which it operates our workshop, our experiences with patients and work methodology.